A theoretical study on CO2 at Li4SiO4 and Li3NaSiO4 surfaces. Issue 22 (25th May 2022) - Gutiérrez, Alberto; Tamayo-Ramos, Juan Antonio; Martel, Sonia; Barros, Rocío; Bol, Alfredo; Gennari, Fabiana Cristina; Larochette, Pierre Arneodo; Atilhan, Mert; Aparicio, Santiago
Abstract : Lithium silicates have attracted great attention in recent years due to their potential use as high-temperature (450–700 °C) sorbents for CO2 capture. Abstract : Lithium silicates have attracted great attention in recent years due to their potential use as high-temperature (450–700 °C) sorbents for CO2 capture. Lithium orthosilicate (Li4 SiO4 ) can theoretically adsorb CO2 in amounts up to 0.36 g CO2 per g Li4 SiO4 . The development of new Li4 SiO4 -based sorbents is hindered by a lack of knowledge of the mechanisms ruling CO2 adsorption on Li4 SiO4, especially for eutectic mixtures. In this work, the structural, electronic, thermodynamic and CO2 capture properties of monoclinic phases of Li4 SiO4 and a binary (Li3 NaSiO4 ) eutectic mixture are investigated using density functional theory. The properties of the bulk crystal phases as well as of the relevant surfaces are analysed. Likewise, the results for CO2 –lithium silicates indicate that CO2 is strongly adsorbed on the oxygen sites of both sorbents through chemisorption, causing an alteration not only in the chemical structure and atomic charges of the gas, as reflected by both the angles and bond distances as well as atomic charges, but also in the cell parameters of the Li4 SiO4 and Li3 NaSiO4 systems, especially in Li4 SiO4 (001) and Li3 NaSiO4 (010) surfaces. The results confirm strong adsorption of CO2 molecules on all the considered surfaces and materials followed by CO2 activation as inferred from CO2 bending, bond elongation and surface to CO2 charge transfer, indicating CO2 chemisorption for all cases. The Li4 SiO4 and Li3 NaSiO4 surfaces may be proposed as suitable sorbents for CO2 capture in wide temperature ranges.